Prenatal linuron exposure disrupts adrenal steroidogenesis and induces adrenal insufficiency in male rat offspring - Duoduo Quan; Yang Cheng; Xinhe Zhou; Jiao Xu; Tingting Shangguan; Yibing Tang; Zhiguang Zhao; Qiang Xu (Current Research in Toxicology)
Linuron, a commonly used agricultural herbicide in certain regions, has raised concerns due to its endocrine toxicity in humans and wildlife. While its gonadal toxicity is established, its direct impact on prenatal adrenal development remains unexplored. Pregnant Sprague-Dawley rats received linuron doses (0, 25, 50, 100 mg/kg/day) by oral gavage from gestational days 12–21. Linuron reduced serum CORT at 50 and 100 mg/kg and ALDO at 100 mg/kg but did not affect ACTH levels. At 100 mg/kg, linuron decreased cell density in the adrenal zona fasciculata without changing its thickness. It also altered the expression of key genes and proteins involved in adrenal function at 50 and/or 100 mg/kg. Additionally, linuron reduced the expression of key antioxidant enzymes (SOD2, GPX1, CAT) at 100 mg/kg. Linuron altered adrenal kinase signaling, activating AMPK but suppressing AKT, with no effect on ERK1/2 pathways. These findings reveal, for the first time, that linuron disrupts male fetal adrenal development and function likely through impaired steroidogenesis, oxidative stress, and dysregulated AKT/AMPK signaling, highlighting its role as a developmental adrenal disruptor.